Influence of Salt and Alkali on Ionic Equilibria in Submerged Soils - Pasricha, N.S.; Ponnamperuma, F.N. (Wiley, 1976)
To clarify the effects of salt and alkali on Fe2+ and Mn2+ equilibria in submerged soils, Maahas clay (a Haplustalf) was amended with NaCl and NaHCO3 to give initial electrical conductivities of 5, 10, 20, and 25 mmhos/cm at 25°C and exchangeable Na percentages of 5, 10, 15, 20, and 25, respectively. The amended soils and an untreated control were kept submerged in 16‐liter pots in a greenhouse at 25–30°C. The soil solutions, drawn anoxically by gravity, were analyzed fortnightly for Eh, pH, CO2, and the major ions. As the salt level increased, pH decreased and the concentrations of all cations increased. As alkalinity increased, the concentrations of all cations except K+ and Na+ decreased. In spite of wide variations in pH, Eh, ionic strength, and the concentrations of Fe2+ and Mn2+ in the soil solutions, the values of the expressions, pE − pFe2+ + 3 pH, pE − 1.5 pFe2+ + 4 pH, pE + pH, and pH − 0.5 pMn2+ − 0.5 pCO2 were nearly equal to 17.9, 23.3, 7.3, and 4.1, respectively, indicating that even in the salt and alkali treated soils, the Fe(OH)3‐Fe2+ and Fe3(OH)8‐Fe2+ systems controlled the solubility of Fe2+ while the MnCO3‐H2O‐CO2 system regulated the solubility of Mn2+.